Prevalence of depression, anxiety, and quality of life among medical students of a tertiary care setting - Panneerselvam Periasamy; Vajiravelu Suganthi; Sasikala Gunasekaran (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Medical school has one of the highest degrees of stress of any educational process. The quality of life and physical and mental health of medical students can be impacted by the rigorous nature of the medical school. The rising morbidity of mental disorders has a significant impact on the academic and professional performance of these students. MATERIALS AND METHODS: The medical students of a tertiary care medical college, Salem, India participated in this cross-sectional study for 3 months between January 2022 and March 2022. All those students who were willing to participate and accepted the informed consent were included in the study. Individuals who denied their consent and with chronic diseases were excluded from the study. RESULTS: Of the total 248 respondents, 149 (60.08%) were females and 100 (39.92%) were males. 27.8% of the study participants belonged in the first year of the MBBS course. Most of the males (35.4%) have normal scoring for depression, whereas 34.2% of females have moderate scoring for depression. DISCUSSION: The students in the 1st year of their study showed higher scoring for depression than in the remaining years, which might be due to less social interactions, new study schedule, and lower grades in the exams than anticipated. CONCLUSION: Making medical students and teachers aware of the detrimental repercussions of excessive levels of depression and anxiety is a necessity of the hour.